About bilingual primary education in Guatemala - Irina Borísovna Kotenyátkina (Ибероамериканские тетради, 2018)
In a knowledge-based society, education is seen as the main source of economic growth. Guatemala is a multilingual country where bilingual education plays an important role because indigenous languages as well as Spanish are in use. In this regard, an educational reform is required to promote bilingual education in order to help indigenous peoples reveal their potential, participate in social and political life, maintain their culture and achieve intercultural coexistence.